2017
DOI: 10.1177/2050640616656708
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of Botulinum toxin in the treatment of chronic anal fissure: 5 years of follow‐up

Abstract: Background: Chronic anal fissure is a frequent and disabling disease, often affecting young adults. Botulinum toxin and lateral internal sphincterotomy are the main therapeutic options for refractory cases. Botulinum toxin is minimally invasive and safer compared with surgery, which carries a difficult post-operative recovery and fecal incontinence risk. The long-term efficacy of Botulinum toxin is not well known. Objective: The aim of this study was to evaluate the long-term efficacy and safety of Botulinum t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 21 publications
(126 reference statements)
2
9
0
2
Order By: Relevance
“…Barberiu et al applied 25 IU toxin in 126 cases where they performed BT and followed the patients for at least 5 years. They achieved complete or partial recovery in 64.8 % of cases and reported no stool leakage [3]. Barnes et al reported a mean of 33 months in 102 cases with ssurectomy +100 IU BT, 7% reported that they had transient anal incontinence, and no recurrence was observed in any of the cases [16].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Barberiu et al applied 25 IU toxin in 126 cases where they performed BT and followed the patients for at least 5 years. They achieved complete or partial recovery in 64.8 % of cases and reported no stool leakage [3]. Barnes et al reported a mean of 33 months in 102 cases with ssurectomy +100 IU BT, 7% reported that they had transient anal incontinence, and no recurrence was observed in any of the cases [16].…”
Section: Discussionmentioning
confidence: 95%
“…The cumulative lifetime incidence is up to 11% throughout life [1]. The most important etiological factor is constipation [2,3]. According to a hypothesis featured by Meegdenburg, trauma is the rst factor in the process of formation and development mechanism of CAFs [4].…”
Section: Introductionmentioning
confidence: 99%
“…2 Con respecto a la toxina botulínicano se encontró una asociación clara entre la dosis, la preparación, el sitio de inyección y las tasas de curación, sumado al elevado costo del tratamiento y la posibilidad igual o mayor al 60% luego de interrumpir el tratamiento. 11 La nifedipina es superior a los nitritos en sus resultados y con menores efectos secundarios e interacciones medicamentosas. 7,8 La tasa de cicatrización de la esfinterotomía lateral es entre el 92 y 100 % con incontinencia del 3,3 al 16 %.…”
Section: Discussionunclassified
“…5,[8][9][10] La esfinterotomía es más eficaz que la toxina botulínica a los 3 años, a pesar de una incontinencia del 9 % con una recurrencia de la toxina botulínica de hasta el 50 % a los 3 años. 11 Los efectos secundarios de los nitritos (cefalea) y la incontinencia asociada a la cirugía, a pesar de su alta efectividad y de algunos reportes de incontinencia transitoria secundaria a la toxina botulínica, deben ser considerados. Sin embargo, y al igual que Nuñez, el tratamiento es efectivo en un alto porcentaje, de difícil acceso por su alto costo de producción, pero de alta adhesión y casi nulos efectos adversos.…”
Section: Discussionunclassified
“…Chronic anal fissure (AF) is an ulcer of the distal anal canal. Fissure causes substantial morbidity in otherwise healthy people [ 1 ]. Most of the fissures are located at the posterior commissure [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%